Microparticle characterization using digital holography - Emmanouil Darakis (2010)
Digital holography is an effective 3D imaging technique, with the potential to be used for particle size measurements. A digital hologram can provide reconstructions of volume samples focused at different depths, overcoming the focusing problems encountered by other imaging based techniques. Several particle analysis methods discussed in the literature consider spherical particles only. With the object sphericity assumption in place, analysis of the holographic data can be significantly simplified. However, there are applications, such as particle analysis and crystallization monitoring, where non-spherical particles are often encountered. This paper discusses the processing of digital holograms for particle size and shape measurement for both spherical and arbitrarily shaped particles. An automated algorithm for identification of particles from recorded hologram and subsequent size and shape measurement is described. Experimental results using holograms of spherical and non-spherical particles demonstrate the performance of the proposed measuring algorithm.